Women blogs and aestheticised consumption - GÜRSOY, AYŞE BİLGE (My University, 2013)
Ideology is a system of ideas that aspires both to explain the world and to change it. Aesthetic founded as a philosophical discipline by A. G. Baumgarten is the science of what is sensed and imagined. The ideology of aesthetics is used to shape subjects and give them a new form. Individuals accept imposed politics or consumption objects, without force when they are aestheticised. For example the fascists aestheticised politics, the global capitalist system aestheticised consumption and created consumption societies. Especially through media, consumption products appeal to senses and are easily accepted. Perceiving consumption as aesthetic; people incline towards consumption and express themselves by the products they consume. This study examines and compares two women blogs: \"Shopping Consultant\" in Turkish and \"A Mom in Red High Heels\" in English. In these blogs, it can be observed that consumers find consumption aesthetic; they are satisfied to have consumer identity. Aestheticised consumption which is created by the \"ideology of aesthetic\", seems global and suitable to global capitalist system\"s needs.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; İktisat; Social Sciences and Humanities; Sociology; Economics; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Ekonomi ve İş; Sosyal Bilimler Genel; EKONOMİ; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; ECONOMICS; Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Genel Sosyal Bilimler; Genel Ekonomi, Ekonometri ve Finans; General Arts and Humanities; Social Sciences & Humanities; General Social Sciences; General Economics, Econometrics and Finance; Aesthetic; Consumption; Women blogs; Aesthetic; Consumption; Women blogs